HCV RNA quantification in capillary dried blood spots with the Xpert® HCV Viral Load test for diagnosing chronic HCV infection, monitoring treatment and detecting reinfection (Swiss Medical Weekly, 2021)
BACKGROUND: For patients with difficult venous access after long-term intravenous drug use, rapid point-of-care hepatitis C virus (HCV) RNA quantification in capillary whole blood with the Xpert® HCV Viral Load Fingerstick (VL FS) test (60 minutes) is a convenient and reliable method for diagnosing chronic HCV infection, monitoring treatment and detecting reinfection. However, an expensive GeneXpert® system must be available on site. In decentralised settings with a low case-load, dried blood spot (DBS) testing might be an alternative.METHODS: Between December 2019 and January 2021, patients with an indication for HCV RNA quantification and informed consent provided 100 µl capillary whole blood each for on-site Xpert® HCV VL FS testing (reference) and DBS testing in the laboratory. For the latter, 100 µl blood, collected with an EDTA Minivette®, were transferred to a Whatman® 903 filter card. After drying for at least 1 hour, the DBS sample was packed into a sealable plastic bag with desiccant and sent to the central laboratory of our hospital, where it was stored at –20°C. For HCV RNA extraction, the whole DBS was cut out with an 18-mm puncher and transferred into 1.3 ml guanidinium thiocyanate-containing buffer (provided by Cepheid®). After mixing and incubating at room temperature for 2–3 hours, 1 ml supernatant was analysed with the Xpert® HCV VL test (105 minutes) (filter paper absorbs 0.3 ml).RESULTS: Of 109 paired samples from 67 patients, 38 (34.9%) were positive with the Xpert® HCV VL FS test. Sensitivity and specificity of DBS testing were 89.5% (34/38; 95% confidence interval [CI] 75.9–95.8%) and 97.2% (69/71; 95% CI 90.3–99.2%), respectively. The six (5.5%) discordant results (four false negative, two false positive) all were observed in samples with HCV RNA detectable below the limit of quantification after 2–8 weeks of pan-genotypic direct-acting antiviral treatment or 5 weeks after acute hepatitis C in a patient clearing HCV spontaneously. Quantifiable results (n = 30; 16 genotype 1, 7 genotype 3, 4 genotype 4, 1 genotype 1a and 3a, 2 unknown; HCV RNA range: 2.74–6.66 log IU/ml) correlated well (R2 = 0.981). On average, uncorrected DBS test results were 1.30 ± 0.14 log IU/ml lower than Xpert® HCV VL FS test results (~42 μl instead of the expected 1000 μl plasma used). Storage of DBS samples at room temperature for 7 days before freezing reduced HCV RNA by 0.29 ± 0.12 log IU/ml.CONCLUSION: HCV RNA can reliably be quantified with the Xpert® HCV VL test in capillary dried blood spot samples. Thus, access to capillary HCV RNA quantification for diagnosing chronic HCV infection, monitoring treatment and detecting reinfection can be extended to decentralised settings with a low case load.